Enhanced lipid production and nutrient utilization of food waste hydrolysate by mixed culture of oleaginous yeast Rhodosporidium toruloides and oleaginous microalgae Chlorella vulgaris. (October 2018) - Zeng, Yu; Xie, Tonghui; Li, Panyu; Jian, Banggao; Li, Xiang; Xie, Yi; Zhang, Yongkui
Abstract: Using food waste hydrolysate as medium for culturing oleaginous microorganism is a dual-purpose strategy for relieving environmental burdens both in food waste disposal and energy crisis. The pure culture of one oleaginous microorganism when single waste as culture media has shortages such as high operation cost, low lipid production and low substrate utilization. Mix-culture of yeast and microalgae in this work enhanced this process result in better waste treatment, higher lipid production and shorter cultivation time. Compare to pure culture of Rhodosporidium toruloides, the nitrogen utilization rate, reducing sugar utilization rate and lipid production increased by 23%, 17% and 12%, respectively, and the cultivation time shorten by 40%, in mix-culture of Rhodosporidium toruloides and Chlorella vulgaris . The results showed that the mix-culture of yeast and microalgae using food waste hydrolysate as culture medium would be a good strategy for both waste disposal and biofuel production. Graphical abstract: Image Highlights: Food waste was used as the sole substrate for the microbial lipid production. Sugar & light affect the balance of heterotrophic & autotrophic metabolism. Mixed culture promoted the substrate utilization by oleaginous microorganisms. Mixed culture enhanced the lipid production and shorten 40% of the cultivation time.